Interferon-gamma release assays for tuberculosis: current and future applications. (February 2014) - Thillai, Muhunthan; Pollock, Katrina; Pareek, Manish; Lalvani, Ajit
Abstract : Interferon-gamma release assays (IGRAs) represent the first new tool to diagnose latent tuberculosis infection for more than 100 years. They have advantages over the traditional tuberculin skin test which has a poor specificity due to false-positive responses in people who are BCG vaccinated as there is a cross-reactivity of proteins present in both BCG and the tuberculin skin test. IGRAs rely on the concept of detecting the ex vivo release of the cytokine IFN-γ, a key anti- Mycobacterium tuberculosis cytokine, from T cells which react specifically to antigens from M. tuberculosis . T cells are sensitized to the antigens in vivo, and then react when they encounter the same proteins ex vivo. The readouts are used to determine presence of sensitized cells, acting as a surrogate for latent tuberculosis infection. IGRAs are now being incorporated into national guidance for diagnosis and research is ongoing into next-generation versions of the test.